Cover Image: Crystalline morphologies at the surface of PET/PEN random copolymer films. Issue 5 (26th March 2020) - Shinotsuka, Kei; Assender, Hazel E.
Crystalline Morphologies of the Surface of Random Copolymer Films: In their work reported in article e10087, Shinotsuka and Assender demonstrate that polymers can crystallize preferentially at the free surface when annealed at temperatures between the surface and bulk glass transition temperatures, forming dendritic structures observable by AFM. This is a near‐surface rather than a thin‐film phenomenon. A 436nm thick 50/50 PET/PEN random copolymer shows surface crystallization at a temperature 90°C lower than bulk crystallization. In 31nm films, the crystallization is affected by the confinement of the thin film and the first stages of crystallization, near the nucleus, form with one morphology (orientation) and then switch to clearer dendrites, likely of edge‐on orientation. (DOI: 10.1002/pcr2.10087 )